Integrating Civilian Agencies in Stability Operations - Szayna, Thomas S. (RAND Corporation, 2009)
How can the Army help make key civilian agencies more capable partners in stability, security, transition, and reconstruction (SSTR) operations? The authors identify the civilian agencies that should be involved in such operations, then locate the necessary skill sets. They then assess the capacity of the civilian agencies to participate in SSTR operations and analyze the recurring structural problems that have plagued their attempts to do so.